2012
DOI: 10.4049/jimmunol.1102892
|View full text |Cite
|
Sign up to set email alerts
|

Heligmosomoides polygyrus bakeri Induces Tolerogenic Dendritic Cells that Block Colitis and Prevent Antigen-Specific Gut T Cell Responses

Abstract: Immunological diseases like IBD are infrequent in less developed countries possibly because helminths provide protection by modulating host immunity. In IBD murine models, the helminth Heligmosomoides polygyrus bakeri (Hpb) prevents colitis. It was determined if Hpb mediated IBD protection by altering DC function. We used a Rag IBD model where animals were reconstituted with IL10-/- T cells making them susceptible to IBD and with OVA antigen-responsive OT2 T cells allowing study of a gut antigenic response. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 38 publications
0
69
0
Order By: Relevance
“…DCs typically acquire regulatory properties in the presence of TGF-b (47). Although the effect of HES in our in vitro cocultures was mainly on the T cells, H. polygyrus and the excretory-secretory products are also know to facilitate regulatory and Th2-promoting DC (31,(48)(49)(50). Interestingly, we found that preconditioning the site of BCG infection with TGF-b or HES significantly reduced BCGtriggered migration of DC (MHC-II hi CD11c +/int cells) to the draining LN.…”
Section: Discussionmentioning
confidence: 47%
“…DCs typically acquire regulatory properties in the presence of TGF-b (47). Although the effect of HES in our in vitro cocultures was mainly on the T cells, H. polygyrus and the excretory-secretory products are also know to facilitate regulatory and Th2-promoting DC (31,(48)(49)(50). Interestingly, we found that preconditioning the site of BCG infection with TGF-b or HES significantly reduced BCGtriggered migration of DC (MHC-II hi CD11c +/int cells) to the draining LN.…”
Section: Discussionmentioning
confidence: 47%
“…Compared to DCs from uninfected animals, intestinal DCs after Hpb infection only weakly support antigen-driven IFNÎł secretion. Furthermore, DCs isolated from the intestines or MLN of Hpb -infected Rag mice transferred into colitis-susceptible block colitis and mucosal antigen-induced, IFNÎł and IL17 responses (27). …”
Section: Mechanisms Of Regulationmentioning
confidence: 99%
“…3 Alternative therapeutic strategies in (pre) clinical development target cytokines involved in IBD pathogenesis (IL-12 and IL-23), the a4b7 integrin involved in lymphocyte homing to the gut, and JAK3 kinase, which is involved in cytokine signaling. 4 Additionally, rather experimental strategies attempt to modulate pathogenic immune responses in models of IBD by the introduction of helminths, such as Heligmosomoides polygyrus 5,6 or Trichuris suis 7,8 or of probiotics (especially Lactobacillus or Bifidobacterium species or the Escherichia coli strain Nissle). 9 Chronic gastric infection with the bacterial pathogen Helicobacter pylori causes gastritis and peptic ulcer disease 10 and represents the most important risk factor for gastric cancer 11,12 but has also been linked inversely to the risk of developing allergic diseases and IBD in large epidemiological studies and Supplemental digital content is available for this article.…”
mentioning
confidence: 99%